WASTAGE MANAGEMENT IN A PRODUCTION CIRCLE: AN EDUCATIONAL INSIGHT (Journal of Association of Educational Management and Policy Practitioners, 2024)
The study wastage management in a production circle: an educational insight adopted an expost-facto survey design. Four research questions and three null hypotheses guided the study. The population of the study is 642 lecturers’ from federal and state universities in south-east Nigeria. The sample size was 311 respondents selected through proportionate stratified random sampling technique representing 50% of the population. Researchers’ self-developed questionnaire titled Wastage Management in Production Circle (WAMAPROC) was used for data collection. The instrument was validated by two experts in economics of education and one expert in measurement and evaluation. Cronbach alpha statistics was used to determine the reliability of the instrument which yielded a reliability index of 0.81which is reliable. Data were analyzed using mean rating and z-test to answer the research questions and test the hypotheses at 0.05 level of significance respectively. The result of the analysis indicates that lecturers’ from federal and state universities are of the view that effective management is relevant in the control of wastage in the university community to ensure effective teaching outcome since the z-cal. of 0.5312< z-crit. Value of 1.96. The study also shows that there is a significant difference on infrastructural wastage and negative teaching and learning outcome since the z-cal. Value of 7.0185> the z-crit. Value of 1.96. Based on the findings of the study, the researchers recommended that the school administrators in the universities should have a managerial blue print for management of school facilities used in teaching-learning activities. That effective management towards quality maintenance culture of infrastructure and other facilities in the university community should be encouraged.